Influence Tactics of Leaders: The Role of Ray Kroc’s Transformational Leadership in Shaping McDonald’s Organizational Culture and Global Success - Muhamad Reza Pahlefy; Tasya Amanda Putri (PT. Hasba Edukasi Mandiri, 2025)
Leadership plays a central role in determining organizational success, especially in the context of competitive global business. Ray Kroc, the figure behind McDonald’s success, is known as a transformational leader capable of turning a small restaurant into a leading global fast-food chain. This study aims to analyze the application of the Model of Power and Influence in Kroc's leadership, particularly in building an organizational culture based on innovation, efficiency, and adaptability. Using a literature review approach, data were obtained from scientific journals, books, and credible reports. The analysis shows that Kroc integrated influence tactics such as rational persuasion, inspirational appeals, and consultation to create commitment, compliance, and overcome resistance within the organization. Innovations such as the Speedee Service System reflect a rational persuasion approach that enhanced operational efficiency. Inspiration was instilled through core values such as Quality, Service, Cleanliness, and Value. Consultation with franchise partners ensured local adaptation without sacrificing global standards. As a result, McDonald’s achieved customer loyalty, employee compliance, and consistent global expansion. Kroc's transformational leadership demonstrates how the application of the Model of Power and Influence can create a highly competitive organizational culture and long-term sustainability. This study emphasizes the importance of combining vision, strategy, and influence tactics in building a successful global organization.